Optimizing the thermal system of electronic equipment using boron arsenide heat sink - N.K. Yurkov; I.M. Rybakov; E.A. Vershinin (Известия высших учебных заведений. Поволжский регион:Технические науки)
Background. In modern radio-electronic equipment one of the most important tasks is optimization of thermal solution to ensure effective heat dissipation and maintenance of optimal operating temperature of devices, devices, products. This is especially relevant in the conditions of constant increase in the density of components and increase in heat dissipation. Technical solutions to optimize the thermal system of radio electronic equipment are becoming increasingly important aspects in the context of increased requirements of external influencing factors to the efficiency and reliability of devices. One of the approaches attracting the attention of researchers is the use of boron arsenide heat sink. The purpose of the study is to develop and optimize the thermal system of radioelectronic equipment with the use of boron arsenide heat sink to ensure stable temperature operation of devices and increase their reliability, durability. Materials and methods. The results obtained on the basis of the analysis of the thermal characteristics of radio electronic components, modeling of heat transfer processes and evaluation of the efficiency of using boron arsenide heat sink in the thermal system are presented. Results. The developed thermal system with the use of boron arsenide heat sink allows to effectively control heat flows and provide optimal operating conditions for radio-electronic equipment. The conducted experiments and calculations confirm the improvement of heat dissipation and reduction of the risk of device overheating. Conclusion. The developed scientific and technical solutions for optimization of the thermal system of radio-electronic equipment with the use of boron arsenide heat sink provide an increase in reliability, durability and efficiency of devices, devices, products, units in conditions of increased external factors.